Glabridin Prevents Doxorubicin-Induced Cardiotoxicity Through Gut Microbiota Modulation and Colonic Macrophage Polarization in Mice - Huang, Keqing; Liu, Yanzhuo; Tang, Honglin; Qiu, Miao; Li, Chenhong; Duan, Chenfan; Wang, Chenlong; Yang, Jing; Zhou, Xiaoyang (Frontiers in Pharmacology, 2019)
The chemotherapeutic drug doxorubicin (DOX) provokes a dose-related cardiotoxicity. Thus, there is an urgent need to identify the underlying mechanisms and develop strategies to overcome them. Here we demonstrated that glabridin (GLA), an isoflavone from licorice root, prevents DOX-induced cardiotoxicity through gut microbiota modulation and colonic macrophage polarization in mice. GLA reduced DOX-induced leakage of myocardial enzymes including aminotransferase, creatine kinase, lactate dehydrogenase, and creatine kinase-MB. GLA downregulated pro-apoptotic proteins (Bax, cleaved-caspase 9 and cleaved-caspase 3) and upregulated anti-apoptotic proteins (HAX-1 and Bcl-2) in the cardiac tissues. In addition, GLA modulated DOX-induced dysbiosis of gut microbiota and thereby decreased the ratio of M1/M2 colonic macrophage, accompanied by the downregulated lipopolysaccharide (LPS) and upregulated butyrate in the feces and peripheral blood. The leakage of myocardial enzymes induced by the DOX was decreased by antibiotics treatment, but not altered by co-treatment with the GLA and antibiotics. The ratio of M1/M2 colonic macrophage and leakage of myocardial enzymes reduced by the GLA were greatly increased by the Desulfovibrio vulgaris or LPS but decreased by the butyrate. Depletion of the macrophage attenuated DOX-induced cardiotoxicity but failed to further affect the effects of GLA. Importantly, GLA decreased production of M1 cytokines (IL-1β and TNF-α) but increased production of M2 cytokines (IL-10 and TGF-β) in the colonic macrophage with the downregulation of NF-κB and the upregulation of STAT6. In summary, GLA prevents DOX-induced cardiotoxicity through gut microbiota modulation and colonic macrophage polarization, and may serve as a potential therapeutic strategy for the DOX-induced cardiotoxicity.